An Investigation on Longitudinal Surface Subsidence Deformation of Large-Span Undercut Metro Tunnel - Yan, Nan; Jing, Desheng; Sang, Songkui; Bai, Xiaoyu; Liu, Xueying; Zhang, Mingyi; Jiao, Yujin; Liu, Honghua; Yan, Jun; Wang, Zhongsheng; Huang, Yongfeng (Frontiers in Earth Science, 2022)
Underground excavation techniques are frequently used in subway stations during the construction of urban rail transit. The current study analyzes and investigates the surface settlement and deformation laws of large-span shallow buried underground excavated stations depending on a vast quantity of measured data from the Qingdao Metro Line 3. According to the comprehensive study, obtained results show that: 1) the excavation of pilot tunnels on both sides will result in the longitudinal settlement at the ground surface; however, the settlement will be quite minor, within −10 mm. During the excavation of the middle part of the pilot tunnel, large surface settlement may occur, and the settlement may reach −30 mm, while during the excavation of the lower soil and construction of the station structure, the surface settlement changes insignificantly, and some monitoring points show a sinking trend. 2) Data fitting reveals that regression analysis with a one variable cubic polynomial produces excellent fitting results. In addition, the analysis based on statistical methods reveals that the conditions of the surrounding rock are poor (Class that the arch, and the overall buried depth of the station is not larger than 10 m. 3) Since the surface settlement control standard for large-span boring tunnels is −60 mm, using −48 mm as the warning value is more reasonable. The test conducted in the current study has helped accumulate a large amount of ground settlement monitoring data, which can provide a particular reference for the subsequent design of similar lines.